2015
DOI: 10.1002/jor.23042
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of the in vivo mechanics of the cervical spine after anterior arthrodesis as revealed by dynamic biplane radiography

Abstract: Arthrodesis is the standard of care for numerous pathologic conditions of the cervical spine and is performed over 150,000 times annually in the United States. The primary long-term concern after this surgery is adjacent segment disease (ASD), defined as new clinical symptoms adjacent to a previous fusion. The incidence of adjacent segment disease is approximately 3% per year, meaning that within 10 years of the initial surgery, approximately 25% of cervical arthrodesis patients require a second procedure to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 87 publications
(156 reference statements)
0
7
0
Order By: Relevance
“…It is well known that the frequent occurrence of cervical spine diseases may be the results of abnormal spinal loading. 11 Thus, knowledge of biomechanical environment of cervical spine is essential for studying the etiology of cervical spinal diseases and for improving current prosthesis testing standard. In this study, the dynamic in vivo joint loading patterns, including intervertebral compressive and shear force and facet joint force, were comprehensively studied using the developed cervical spine MSK MBD model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the frequent occurrence of cervical spine diseases may be the results of abnormal spinal loading. 11 Thus, knowledge of biomechanical environment of cervical spine is essential for studying the etiology of cervical spinal diseases and for improving current prosthesis testing standard. In this study, the dynamic in vivo joint loading patterns, including intervertebral compressive and shear force and facet joint force, were comprehensively studied using the developed cervical spine MSK MBD model.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The investigation of kinematics and kinetics of cervical spine, during the various head motion, will contribute to understand the pathogenesis of the adjacent segment disease, to study in vivo wear and sagittal imbalance. 10,11 However, direct acquisition of in vivo cervical spinal loading is not yet an easy task. Traditionally, spinal compressive forces are obtained by the conversion of intradiskal pressure (IDP) results.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent reports indicate that in vitro models fail to accurately predict clinical outcomes 5 . This may be due in part to an inability to accurately replicate in vivo motion characteristics beyond simple ROM measures 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 This may be due in part to an inability to accurately replicate in vivo motion characteristics beyond simple ROM measures. 6 Various loading techniques have been developed in an attempt to perform material property testing on spines or to replicate in vivo spine kinematics and loading. In pure moment (PM) loading, the moment applied to the end vertebra is applied equally to all segments of the specimen.…”
mentioning
confidence: 99%
“…Therefore, understanding of the spinal biomechanics is critically important for investigation of the mechanisms of cervical spine disc diseases and for development of treatment modalities to restore neck function. However, a literature review indicated that few studies have been reported on the biomechanics of the cervical spine discs [16]. For example, sagittal plane magnetic resonance (MR) or plane X-ray images have been used to investigate disc space heights at nonweightbearing supine or weightbearing standing positions [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%